Enhanced skin delivery of vismodegib-loaded rigid liposomes combined with ethosomes - E.T. Aguayo Frías; D. Maza Vega; M.N. Calienni; C. Lillo; D.S. Vazquez; S.d.V. Alonso; J. Montanari (Elsevier, 2023)
Vismodegib, first approved in 2012 for the treatment of basal cell carcinoma, is an inhibitor of the Hedgehog signaling pathway that becomes active in certain tumors. However, its secondary effects after oral administration and systemic distribution are severe. In this study, we loaded vismodegib into conventional liposomes, which are typically unable to penetrate the stratum corneum barrier effectively after topical application. We studied its skin penetration when co-administered with empty ethosomes, aimed at transiently disrupting the skin impermeability.The drug was successfully recovered from the deeper viable epidermal layers in an in vitro model. The preparation method for the liposomal formulation is reproducible and relatively straightforward to scale up. Furthermore, it involves the use of biocompatible lipids, thus avoiding the utilization of potentially risky compounds.